Aluminium Chloride‐Mediated Synthesis of 1‐Chloro‐2, 2, 2‐Trifluoroethylidene‐Substituted Pyrrolidones. Issue 11 (19th April 2018) - Wang, Zeng; Yuan, Zihang; Han, Xiaoyan; Weng, Zhiqiang
Abstract: An aluminium chloride‐mediated cascade reaction between pyrrolidones and trifluoroacetic anhydride is reported. Functionally diverse 1‐chloro‐2, 2, 2‐trifluoroethylidene‐substituted pyrrolidones were obtained in moderate to high yields through electrophilic trifluoroacetylation, nucleophilic chlorination, and elimination. This procedure has a wide scope, good functional‐group tolerance and the reaction conditions are amenable to scale up. Additionally the obtained 1‐chloro‐2, 2, 2‐trifluoroethylidene products can be applied to further functionalization as trifluoromethyl‐containing building blocks. Some of the title compounds showed fungicidal activity against cucumber downy mildew (CDM). Abstract :